Atividade antifúngica in vitro de timol sobre cepas do gênero Penicillium - Dantas, Tassiana Barbosa (2013)
The fungi have become, over the last two decades, a major cause of illness in humans. Fungi of the genus Penicillium can be found in various substrates and affect immunocompromised people, hospitalized patients, many animals and plants, as well as compromise the quality of air indoors. The indiscriminate use of antibiotics and the resulting framework of resistance of microorganisms to conventional antimicrobial therapy has been stimulating researchers to seek alternative sources of these compounds, among them products derived by medicinal plants. Tendency to get phytochemicals from extracts, fractions, fixed or essential oils obtained from plant species is currently observed. In this context, the present study evaluated the in vitro antifungal activity of seven phytochemicals: carvacrol, citral, geraniol, linalool, pcymene, terpinolene and thymol, against twelve strains of Penicillium. Firstly, screening was carried out to find the phytochemical with the best activity by determining the Minimum Inhibitory Concentration (MIC) by the broth microdilution technique. Following, the tests were proceeded with thymol, which were: determination of Minimum Fungicidal Concentration (MFC), effect of the phytochemical on mycelial growth kinetics, interference of thymol on germination of conidia and evaluation of the influence of thymol on the fungal morphology. To this end, we selected two strains, one that was more resistant and another with a more sensitive profile. The value of thymol MIC50 and MIC90 was 128μg/ml, while the CFM value ranged from 128μg/ml to 1024μg/ml. It was observed total radial mycelial growth inhibition at the three thymol concentrations used (128μg/ml, 256μg/ml and 512μg/ml) over 14 days of exposure. In the study of the interference of thymol on the conidia germination was observed inhibitory effect. At the concentration of 512μg/mL was found greater than 80% inhibition, at 256 μg/mL inhibition was higher than 75%, while in 128μg/mL inhibition was higher than 60%, all this for both strains tested, revealing concentration-dependent inhibitory effect. In the presence of thymol, morphological changes were observed in mycelial structure, such as decrease in the amount of conidia, reduction in the formation of reproductive structures with the appearance of rudimentary reproductive structures, besides the abnormal development of hyphae. Given the above, it is concluded that thymol has antifungal activity against strains of Penicillium and therefore represents a new possibility in the arsenal of products for the treatment of infections caused by this fungus.